Analysis of Efforts to Prevent Dermatitis in Coastal Communities in Kampung KB, Dusun 15, Tanjung Rejo Village, Percut Sei Tuan District, Deli Serdang District - Dewi Agustina; Adinda Dwi Firia; Anisa Ayu Lestari; Nasywa Nazhifah; Restu Amalia Mazid; Rizka Sahilla; Shopiah Auzi; Yayang Nisrina Putri Hasibuan (Sean Institute, 2024)
Dermatitis, which is often known as an inflammatory skin reaction, is a condition that commonly occurs among coastal communities in areas such as Kampung KB, Dusun 15, Tanjung Rejo Village, Percut Sei Tuan District, Deli Serdang Regency. Unique environmental factors and lifestyles associated with coastal living can be major triggers for the onset of this disease. This research aims to provide knowledge to the community regarding the prevention of dermatitis in KB Village, Hamlet 15, Tanjung Rejo Village, Percut Sei Tuan District, Deli Serdang Regency. This type of research is analytical survey research using a Cross Sectoinal Study design. This research was conducted in KB Village, Hamlet 15, Tanjung Rejo Village, Percut Sei Tuan District, Deli Serdang Regency. The population in this study were fishermen in KB Village, Hamlet 15, Tanjung Rejo Village, Percut Sei Tuan District, Deli Serdang Regency with a total of 10 fishermen as respondents. The instruments used in this research were skin disease symptom and personal hygiene questionnaires. The results of the research show that the majority of respondents have good knowledge about dermatitis and also 90% of the majority of respondents from coastal communities have good personal hygiene and there is a significant relationship between knowledge and efforts to prevent dermatitis in coastal communities.